Intra‐fractional patient motion when using the Qfix Encompass immobilization system during HyperArc treatment of patients with brain metastases. Issue 3 (3rd March 2021) - Komiyama, Riho; Ohira, Shingo; Ueda, Hikari; Kanayama, Naoyuki; Masaoka, Akira; Isono, Masaru; Ueda, Yoshihiro; Miyazaki, Masayoshi; Teshima, Teruki
Abstract: Purpose: This study investigated the intra‐fractional motion (IM) of patients immobilized using the QFix Encompass Immobilization System during HyperArc (HA) treatment. Method: HA treatment was performed on 89 patients immobilized using the Encompass. The IM during treatment (including megavoltage (MV) registration) was analyzed for six degrees of freedom including three axes of translation (anterior‐posterior, superior‐inferior (SI) and left‐right (LR)) and three axes of rotation (pitch, roll, and yaw). Then, the no corrected IM (IMNC ) was retrospectively simulated (excluding MV registration) in three directions (SI, LR, and yaw). Finally, the correlation between the treatment time and the IM of the 3D vector was assessed. Results: The average IM in terms of the absolute displacement were 0.3 mm (SI), 0.3 mm (LR) and 0.2° (yaw) for Stereotactic radiosurgery (SRS), and 0.3 mm (SI), 0.2 mm (LR), and 0.2° (yaw) for stereotactic radiotherapy (SRT). The absolute maximum values of IM were <1 mm along the SI and LR axes and <1° along the yaw axis. The absolute maximum displacements for IMNC were >1 mm along the SI and LR axes and >1° along the yaw axis. In the correlation between the treatment time and the IM, the r ‐values were −0.025 and 0.027 for SRS and SRT respectively, along the axes of translation. For the axes of rotation, the r ‐values were 0.012 and 0.206 for SRS and SRT, respectively. Conclusion: Encompass provided patient immobilization with adequate accuracy during HA treatment. The absolute maximum displacement IM was less than IMNC along the translational/rotational axes, and no statistically significant relationship between the treatment time and the IM was observed.